KEDALAMAN LUBANG INOKULASI DAN UKURAN DIAMETER POHON UNTUK PEMBENTUKAN GUBAL GAHARU PADA TANAMAN Aquilaria malaccensis Lamk. - Sari, Suci Indah; Muin, Abdurrani; Suryantini, Rosa (JURNAL HUTAN LESTARI, 2019)
Research on the induction of the sapwood of agarwood has been extensively studied, but this has not yet resulted in the dept standard of hole of inoculation and the diameter of trees in order to produce the best sapwood. Therefore, this study aimed to study the depth of the effective inoculation hole to accelerate the formation of agarwood cambium or sapwood in various tree diameters, and to know the interaction of agarwood induction. This research was conducted in Sekadau Hilir district. The design of this research was a nested method. The treatment consisted of tree diameter (i.e., 11.46 cm, 16.56 cm, and 24.20 cm) as the main factor, while the depth of the inoculation hole (i.e., 1 cm, 2 cm, 3 cm, 4 cm, and 5 cm) was the second nesting factor. The hole spacing was 15 cm, which was in each treatment, the depth of the inoculation hole was repeated 5 times. The number of holes consisted of 75. In which the depth of inoculation hole was 3 cm producing an infection on area of 485.13 cm2, brown, and with strong aroma. Tree diameter of 11.46 cm produced 872.92 cm2 of infected area, blackish brown, and with strong aroma. However, the interaction of tree diameter and the dept of hole was not significant toward the area of agarwood infection formed.Keyword: Agarwood, Aquilaria malaccensis, inoculation